Spatial egalitarianism as a social ï¿½counter-movement': on socio-economic reforms in Chongqing - Lim, Kean Fan (Routledge, 2014)
Through a framework drawn from Karl Polanyi's substantivist theorization of economic practices, this paper evaluates the quest for equitable urbanization in Chongqing, a major city-region in south-western China. Illuminating the tensions arising from two interrelated reforms, namely the ambitious attempt to construct 40 million mÂ² of public rental housing between 2010 and 2012, and the large-scale drive to ensure peasant migrants enjoy equal access to social benefits as current urban residents, the paper explains how the quest for equitable urbanization magnifies two nationwide dimensions of institutionalized uneven development, namely 1) the caste-like categorization of populations according to ï¿½urbanï¿½ and ï¿½ruralï¿½; and 2) the coastal bias in national economic development. The paper concludes that this state-driven pursuit of spatial egalitarianism in Chongqing expresses the dialecticism of economic development in China: it is a social ï¿½counter-movementï¿½ against the effects of an uneven spatiality that was instituted to drive and deepen the marketization of Chinese society.